2012
DOI: 10.1016/j.jcmg.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Napkin-Ring Sign Indicates Advanced Atherosclerotic Lesions in Coronary CT Angiography

Abstract: The assessment of the plaque pattern improves diagnostic accuracy of CCTA to identify advanced atherosclerotic lesions. The CCTA finding of NRS has a high specificity and high positive predictive value for the presence of advanced lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 215 publications
(125 citation statements)
references
References 43 publications
2
123
0
Order By: Relevance
“…1b). The specificity of this NRS for detecting vulnerable plaque is relatively high based on autopsy studies but the sensitivity of this sign is low (6). segments in 895 subjects (mean: 2.…”
Section: Current Status Of Plaque Imaging Using Coronary Ct Angiographymentioning
confidence: 99%
“…1b). The specificity of this NRS for detecting vulnerable plaque is relatively high based on autopsy studies but the sensitivity of this sign is low (6). segments in 895 subjects (mean: 2.…”
Section: Current Status Of Plaque Imaging Using Coronary Ct Angiographymentioning
confidence: 99%
“…Several histology and intravascular-based imaging studies have shown that CTCA allows accurate evaluation of the luminal and outer vessel wall dimensions, assessment of plaque burden and remodeling pattern, and characterization of its composition [85][86][87][88][89][90][91][92]. Reports have demonstrated that CTCA enables detection of calcific tissue but it has a limited accuracy in differentiating lipid from fibrotic tissue component [86,87,89,91,92]; while recent histology-based studies have shown that CTCAdespite its limited imaging resolution -allows characterization of the phenotype of the plaque and detection of high-risk vulnerable lesions -which on CTCA exhibit a napkin-ring sign morphology -with high specificity but low sensitivity [93,94].…”
Section: Computed Tomographic Coronary Angiographymentioning
confidence: 99%
“…14,15 Although CCTA can provide accurate 3D anatomic evaluation of the coronary arteries, determining the extent of luminal stenosis with plaque morphology characterization, numerous studies comparing CCTA-and ICA-assessed stenoses with invasive FFR determination demonstrated that the severity of coronary lesions does not always reflect the hemodynamic significance of a plaque. [16][17][18][19] Meijboom et al evaluated 89 lesions which caused ≥50% luminal stenosis assessed by CCTA and concluded that only 49% of these lesions were functionally significant, with a measured FFR <0.75. 20 Having these aforementioned tools, the development of a noninvasive technique that is able to offer both anatomical and functional evaluation of coronary lesions was imperative.…”
Section: The Need For Noninvasive Ffr Determinationmentioning
confidence: 99%